Interspecies interaction and effect of co-contaminants in an anaerobic dichloromethane-degrading culture. (February 2020) - Trueba-Santiso, Alba; Fernández-Verdejo, David; Marco-Rius, Irene; Soder-Walz, Jesica M.; Casabella, Oriol; Vicent, Teresa; Marco-Urrea, Ernest
Abstract: An anaerobic stable mixed culture dominated by bacteria belonging to the genera Dehalobacterium, Acetobacterium, Desulfovibrio, and Wolinella was used as a model to study the microbial interactions during DCM degradation. Physiological studies indicated that DCM was degraded in this mixed culture at least in a three-step process: i) fermentation of DCM to acetate and formate, ii) formate oxidation to CO2 and H2, and iii) H2 /CO2 reductive acetogenesis. The 16S rRNA gene sequencing of cultures enriched with formate or H2 showed that Desulfovibrio was the dominant population followed by Acetobacterium, but sequences representing Dehalobacterium were only present in cultures amended with DCM. Nuclear magnetic resonance analyses confirmed that acetate produced from 13 C-labelled DCM was marked at the methyl ([2– 13 C]acetate), carboxyl ([1– 13 C]acetate), and both ([1, 2– 13 C]acetate) positions, which is in accordance to acetate formed by both direct DCM fermentation and H2 /CO2 acetogenesis. The inhibitory effect of ten different co-contaminants frequently detected in groundwaters on DCM degradation was also investigated. Complete inhibition of DCM degradation was observed when chloroform, perfluorooctanesulfonic acid, and diuron were added at 838, 400, and 107 μM, respectively. However, the inhibited cultures recovered the DCM degradation capability when transferred to fresh medium without co-contaminants. Findings derived from this work are of significant relevance to provide a better understanding of the synergistic interactions among bacteria to accomplish DCM degradation as well as to predict the effect of co-contaminants during anaerobic DCM bioremediation in groundwater. Graphical abstract: Image 1 Highlights: Several bacteria are involved in the anaerobic metabolism of dichloromethane (DCM). Interspecies H2 transfer observed in the form of acetogenesis in DCM degradation. Inhibition of DCM degradation by chloroform, perfluorooctanoic acid and diuron. Inhibited bacterial cultures can degrade DCM upon removal of the inhibitor.